Construção e validação de filme educativo sobre prevenção de lesão por pressão para cuidadores de idosos - Aguiar, Elizabeth Souza Silva de (2020)
It´s essential to promote health education strategies for caregivers of the elderly regarding the prevention of pressure injuries, in order to minimize the occurrence of these injuries in the elderly. Objective: To develop an educational film for caregivers of the elderly about the prevention of pressure injuries in the elderly with loss of physical mobility. Materials and Method: This is a methodological study, for the development and validation of an educational technology, an educational film in the documentary format. For the development of the film, three phases were followed: pre-production, production and post-production. The film takes place in two real settings - a long-term care facility for the elderly and a home. The target population of the film is formal caregivers and family caregivers for the elderly. Results of the study phases: Phase 1 of pre-production was organized in three subsequent steps - Content of the script of the film, Technical elements of the pre-production and Validation of the script. The content of the script gave the film a theoretical basis, based on guidelines and concepts of caring for Collière, and experiences in different contexts of care for the elderly with reduced physical mobility. The stage of the pre-production elements was related to the creation of the film's script, a basic stage, as it writes the audiovisual project on paper. In the stage of validating the script, two groups of experts were invited to evaluate the script for the film - the area of nursing and social communication. The group of nursing judges participated in the content validation, with seventeen professionals in the first round of validation and ten professionals in the second round. Technical validation was carried out in just one round by three media judges. To validate the instruments, the Content validity index was calculated, with a score greater than 0.80 being considered appropriate. In addition, it was considered pertinent to consider the suggestions of the judges with a view to improving the script. Phase 2 of production, consisted of a single stage with the selection of scenarios and characters, the preparation and recording of the scenes. In post-production phase 3, the film was edited and finalized, with the first finished version of the film being evaluated by invited judges and a new edition was carried out, at the end of which the film was validated by the target audience. Final considerations: The development of this audiovisual material elucidated three pillars of paramount importance for the completion of the film and the achievement of the study objectives: 1) the theoretical basis from the guidelines for the prevention of LP and from the concepts of caring for Collière, 2) the experiences in different care contexts for the elderly with reduced physical mobility and 3) methodological rigor (validation process). Therefore, resulting in a reliable health education tool for family and formal caregivers of the elderly, which can be used in different contexts of care for the elderly with reduced mobility.